Karakteristik Morfologi Gabah dan Beras Padi Lokal (Oryza sativa L.) Asal Lombok, Sumbawa, Kalimantan Timur dan Kalimantan Utara - Fitriani, Fitriani; Aryana, I Gusti Putu Muliarta; Sudika, I Wayan (LPPM Universitas Mataram, 2025)
This study aims to determine the morphological characteristics of local rice grains and rice from Lombok, Sumbawa, East Kalimantan, and North Kalimantan. This research was conducted in May-October 2024, in lowland rice fields and laboratories. The method used was experimental method with RAK 15 treatments 3 replications. The results showed that there were 6 functional local rice varieties, including 4 local black rice varieties namely G1 (Baas Selem), G3 (Ketan Hitam Tampak Siring), G8 (Padi Hitam Kalimantan Utara), and G15 (Padi Hitam Kaltim) and 2 local red rice varieties namely G4 (Beak Ganggas) and G7 (Padi Merah Kalimantan Utara). Local rice varieties that have hair on the tip of the grain are G4 (Beak Ganggas), G6 (Padi Alas), G11 (Ambuyu Merah), dan G15 (Padi Hitam Kaltim). Local variety G4 (Beak Ganggas) showed the highest 100-grain weight of 3,98 gr, so it can be used as an elder in breeding programs to increase yield.